EFFECT OF DAMP AND TREATMENT METHODS ON RESIDENTIAL BUILDINGS IN CALABAR METROPOLIS OF CROSS RIVER STATE - Emmanuel Ubi, Stanley; Obun, Paul Nkra; Reagan B, Agbor; Tom, Thankgod; Agbor, Monday (International Journal of Research -GRANTHAALAYAH, 2020)
The main purpose of this study was to investigate the effect of damp and treatment methods on residential buildings in Calabar Metropolis of Cross River State. Damp is a pervasive problem for residential buildings. It is at times expressed in the most unlikely places under unexpected and unsettling conditions due to heavy rainfall. It is usually expressed at home, market, and neighborhood or within community. At different-occasions damp had cause many damages to school properties, destruction of roads especially during rainy season. To achieve the purpose of this study two research questions were formulated to direct the study. Survey research design was adopted for the study. A sample of one hundred respondents was randomly selected for the study. The selection was done through the simple random sampling technique. This was to give equal and independent opportunities to all the respondents to be selected for the study. The questionnaire was the instrument used for data collection. The instrument was subjected to face validation by experts in measurement and evaluation. The reliability estimate of the instrument was established through the test re-test reliability method. The results of the respondents reveal that damp and treatment method significantly influence residential buildings in Calabar Metropolis. Based on the findings, it was recommended among others that the State government should construct good drainage system to enhance the free flow of stagnant water during or after rainfall in order not to cause damages to the buildings.